Thymic Carcinoma: A Review - Alqaidy, Doaa; Moran, Cesar A. (Frontiers in Oncology, 2022)
The diagnosis of thymic carcinoma may pose significant problems not necessarily in the histopathological diagnosis but rather in assigning the thymus as specific origin. Often the tissue available for interpretation is obtained via a mediastinocopic biopsy, which raises two different issues -minimal tissue and lack of specific features to make a carcinoma of thymic origin. In addition, if to that conundrum we add that there is no magic immunohistochemical stain that will unequivocally lead to the interpretation of thymic carcinoma, then we are left with a true clinical-radiological-pathological correlation. In this review, we will highlight some of those challenges that diagnostic surgical pathologists may encounter in the histopathological assessment of thymic carcinoma as well as in the staging of these tumors.